2022
DOI: 10.1073/pnas.2208814119
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Lonsdaleite to Diamond Formation in Ureilite Meteorites via In Situ Chemical Fluid/Vapor Deposition

Abstract: Ureilite meteorites are arguably our only large suite of samples from the mantle of a dwarf planet and typically contain greater abundances of diamond than any known rock. Some also contain lonsdaleite, which may be harder than diamond. Here, we use electron microscopy to map the relative distribution of coexisting lonsdaleite, diamond, and graphite in ureilites. These maps show that lonsdaleite tends to occur as polycrystalline grains, sometimes with distinctive fold morphologies, partially replaced by diamon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Recently, Tomkins et al. (2022) showed direct evidence for the presence of crystallites of lonsdaleite within two ureilites. Using real‐time in situ synchrotron XRD measurements during impact experiments on high‐order pyrolitic graphite, Turneaure et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Tomkins et al. (2022) showed direct evidence for the presence of crystallites of lonsdaleite within two ureilites. Using real‐time in situ synchrotron XRD measurements during impact experiments on high‐order pyrolitic graphite, Turneaure et al.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of diamond in some weakly shocked ureilites (Miyamoto et al, 1988;Nakamuta & Aoki, 2000;Takeda et al, 2001) also support a vapor-growth mechanism for the origin of diamond. Recently, Tomkins et al (2022) observed the presence of polycrystalline aggregates of lonsdaleite with folded texture within two ureilites. They concluded that the lonsdaleite, diamond, and graphite assemblage formed through a CVD process by reaction between a C-H-O-S fluid/gas with graphite after the impact disruption of the ureilite parent body.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
See 3 more Smart Citations